El manejo forestal del bosque secundario como alternativa de uso de la tierra en la zona norte de Costa Rica - Villalobos-Chacón, Ronny (2022)
Secondary forests have great management potential as a generator of resources and services for society. Wood production remains a widely used resource and a viable alternative. The present study was carried out in three secondary forests in the Huetar Norte region of Costa Rica, in the towns of Florencia, Pénjamo de Florencia and Agua Zarcas. These forests have been evaluated for two decades and silvicultural treatments were applied to them, however, their effect on the forest mass was never evaluated, for this reason this study aims to: evaluate the effect of the application of silvicultural treatments on commercial species. From a diagnosis of sampling and measurement of permanent plots, changes were estimated due to the effect of the application of treatments in the floristic composition, structure, dasometric increases in commercial and non-commercial species; changes on the outstanding desirable leaders were evaluated, the estimates were compared with the forest control in Florencia and Pénjamo only. The three forests presented satisfactory changes in their dasometric variables, structure and composition attributed to the effect on the application of treatments and their previous management, however, it is important to intervene again and monitor their behavior periodically.